IDENTIFIKASI TINGKAT KESIAPAN SISWA DALAM MELAKSANAKAN PRAKTIK KERJA LAPANGAN DITINJAU DARI ASPEK PENILAIAN PRAKTIK KERJA LAPANGAN DI SMK NEGERI 8 MUARO JAMBI - Nuramita; Yanto; Affan Yusra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the level of readiness of twelfth-grade students at SMK Negeri 8 Muaro Jambi in carrying out Field Work Practice (PKL) in terms of attitudes, knowledge, and skills aspects. The problem underlying this study is the importance of student readiness before carrying out Field Work Practice so that students are able to adapt to the work environment and perform practical tasks optimally. This study used a quantitative approach with a descriptive method. The research subjects consisted of 98 students selected using a cluster random sampling technique from a population of 129 students. The research instrument was a Field Work Practice readiness questionnaire. Data analysis was carried out using percentage formulas. The results showed that the overall level of student readiness in carrying out Field Work Practice was in the high category with a percentage of 83%. In terms of the attitude aspect, a percentage of 86% was obtained in the high category. In the knowledge aspect, a percentage of 71% was obtained in the high category, but it was at the lower limit, indicating that students’ understanding still needs to be improved. Meanwhile, in the skills aspect, a percentage of 83% was obtained in the high category. Thus, the readiness level of twelfth grade students at SMK Negeri 8 Muaro Jambi in carrying out Field Work Practice in terms of attitudes, knowledge, and skills aspects is categorized as high.